Factors associated with improvement of quality of life among parents of children with atopic dermatitis: 1‐year prospective cohort study. (10th October 2019) - Maksimovic, N.; Zaric, M.; Reljic, V.; Nikolic, M.; Gazibara, T.
Abstract: Background: Previous studies exploring the impact of atopic dermatitis (AD) in children focused on factors associated with parental quality of life at one point in time. Objective: To examine factors associated with change of quality of life among parents of children affected with AD. Methods: The study cohort comprised 98 parent–children pairs treated for AD at the Clinic of Dermatovenereology; however, 18 parents (18.4%) were lost to follow‐up after 1 year. Children were assessed with SCORing Atopic Dermatitis Index (SCORAD) and Children Dermatology Life Quality Index (CDLQI) or the Infants' Dermatitis Quality of Life Index (IDQOL), depending on their age. Parents filled in socio‐demographic questionnaire and Dermatitis Family Impact Questionnaire (DFI). After 1 year, both children and parents were reassessed using the same AD‐related battery of questionnaires. Results: After follow‐up, a significant improvement in the average total DFI score was observed, especially for domains of fatigue/exhaustion, emotional distress and impact of helping in child treatment. Lower baseline SCORAD, greater improvement of SCORAD over follow‐up, better CDLQI/IDQOL at baseline, greater improvement in CDLQI/IDQOL over follow‐up, not having asthma and having older child with AD were associated with better parental quality of life after 1 year of follow‐up. Parental higher education level, shorter AD duration, better baseline SCORAD and greater improvement in CDLQI/IDQOL over follow‐up were associated with greater improvement in parental life quality over 1 year of follow‐up. Conclusion: Contributors to parental quality of life after 1 year included clinical features of AD and child's comorbidity (asthma), but also the perception of child's quality of life and its improvement.